1989
DOI: 10.1007/bf02306491
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of ocular toxoplasmosis

Abstract: We performed a prospective multicentre study to evaluate the efficacy of therapeutic strategies currently used for ocular toxoplasmosis in a large number of patients (n = 106). Treatment was given for at least four weeks and consisted of three triple drug combinations: group 1, pyrimethamine, sulphadiazine and corticosteroids (n = 29); group 2. clindamycin, sulphadiazine and corticosteroids (n = 37); and group 3. cotrimoxazole (trimethoprim and sulphamethoxazole) and corticosteroids (n = 8). Patients with peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
83
1
14

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 13 publications
2
83
1
14
Order By: Relevance
“…The fourth group (patients with peripheral lesions only) was not treated systemically. Overall the study found that duration of disease related to the size of the initial inflammatory focus regardless of treatment, that pyrimethamine was slightly better at reducing the size of the retinal scar than other agents, but that it also had the highest occurrence of adverse events and that there was no difference in the recurrence rates at three years in any of the groups (Rothova et al 1993). They found no evidence that their therapy altered the inflammatory activity of the disease, despite the use of systemic corticosteroids, that patients who presented late (from 48 h to more than one week after the onset of symptoms) fared differently to those who presented early and that there was no difference whether the patient were presenting for the first time or with recurrent disease.…”
Section: Available Agentsmentioning
confidence: 84%
See 1 more Smart Citation
“…The fourth group (patients with peripheral lesions only) was not treated systemically. Overall the study found that duration of disease related to the size of the initial inflammatory focus regardless of treatment, that pyrimethamine was slightly better at reducing the size of the retinal scar than other agents, but that it also had the highest occurrence of adverse events and that there was no difference in the recurrence rates at three years in any of the groups (Rothova et al 1993). They found no evidence that their therapy altered the inflammatory activity of the disease, despite the use of systemic corticosteroids, that patients who presented late (from 48 h to more than one week after the onset of symptoms) fared differently to those who presented early and that there was no difference whether the patient were presenting for the first time or with recurrent disease.…”
Section: Available Agentsmentioning
confidence: 84%
“…Since the goal of therapy is to alter the natural history of the disease, it is worth examining studies where this has been reported. Rothova et al (1993) carried out a prospective non-randomised study looking at the efficacy of therapy for ocular toxoplasmosis in 149 patients divided into four groups. Group 1 received pyrimethamine, sulfadiazine and corticosteroids; group 2, clindamycin, sulfadiazine and corticosteroids; and group 3, trimethoprim, sulphamethoxazole and corticosteroids.…”
Section: Available Agentsmentioning
confidence: 99%
“…There are no convincing reports on the efficacy of various regimens. While Soheilian et al (2005) reported no difference in the efficacies of trimethoprim/sulphamethoxazole versus pyrimethamine (25 mg, instead of traditional 50 mg) and sulphadiazine in terms of reduction in retinal lesion size and improvement in visual acuity, Rothova et al (1993) had reported marginally superior performance of pyrimethamine in reducing the size of the retinal scar, but also had higher adverse events.…”
Section: Discussionmentioning
confidence: 98%
“…The use of corticosteroids in the treatment of OT has been debated (Bosch-Driessen and Rothova 1998). Given alone, it is known to cause fulminant ocular toxoplasmosis, and used as an adjunct to antiparasitic therapy, it has failed to alter the inflammatory activity of the disease (Rothova et al 1993). However, it is generally accepted in clinical practice that corticosteroids should be a part of treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Makula lezyonlar› konjenital toksoplazmozisin bir göstergesi olarak de¤erlendirilir. Ancak konjenital ve akkiz enfeksiyonun güvenilir bir flekilde ay›rt edilmesini sa¤lamaz (8,9 (12)(13)(14). Hipersensitivite reaksiyonu retina damarlar›ndan s›zan proteinlerden kaynaklanmaktad›r.…”
Section: Tart›flmaunclassified